TREATMENT OF FIRST DEGREE ENDOMETRITIS BY CLOPROSTENOL AND ESTRADIOL IN CHOOLISTANI COWS - M. S. Akhtar; A. A. Farooq; S. Inayat (Journal of Animal and Plant Sciences, 2009)
The present study was planned to know the efficacy of colprostenol (PGF2α analogue) and estradiol for the treatment of endometritis in Cholistani cows. A total of 140 cows were divided into four equal groups (A, B, C, D). Group-A and B was given 2ml Prostenol intramuscularly. After Prostenol treatment, group A (n = 35) animals were inseminated during 1st estrus where as in group-B (n=35), first oestrus expected to occur after 24-94 hours was missed and during subsequent oestrus, animals were inseminated with frozen semen. In group-C (n=35), intrauterine infusions of estradiol 17-β (Star Laboratories) were given for 3 alternative days. For each intrauterine infusion 0.5mg of stilbesterol was thoroughly mixed in 69.5ml of distilled water. Cured animals with normal uterine discharge were inseminated with frozen semen. Group-D (n=35) was given no treatment and served as control. In groups A, B, and C, the curative percentages were 74.28, 88.57 and 62.85 where as the conception rates in all four groups (A, B, C, D) were 65.38, 77.41, 63.63, 40.0 %, respectively. There was significant difference in curative as well as conception rates of group A, B and C as compared to control. Significant difference (P<0.05) was observed between group A and group B in curative as well conception rates. In the present study, the curative and conception rates were higher (P<0.05) with cloprostenol treatment than estradiol treated animals. It was concluded that the use of cloprostenol is more effective as compared to estradiol for the treatment of Ist degree of endometritis in Cholistani cows. After cloprostenol treatment animal should be inseminated during the IInd oestrus that follows the induced one. This will increase curative as well as conception percentage.
Keywords: Cholistani Cow; Endometritis; Cloprostenol; Estradiol